2011
DOI: 10.3928/01477447-20110627-27
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Villonodular Synovitis After TKA Associated With Tibial Component Loosening

Abstract: There is no known causal link between total knee arthroplasty (TKA) and pigmented villonodular synovitis (PVNS). There also is no known relationship between PVNS and implant loosening after TKA in the literature. This article presents a case of PVNS in a patient undergoing revision TKA for tibial component loosening. A 74-year-old woman who had undergone cemented bilateral TKA 5 years earlier presented with painful swelling in her right knee. At the time of the primary TKA, no abnormal signs were found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The causal relationship between TKA and PVNS remains unknown. In addition, it has not been explained how failure and loosening after TKA is caused by PVNS 13 . An idiosyncratic reaction in certain patients to fine wear debris was assumed in the single case described so far 8 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The causal relationship between TKA and PVNS remains unknown. In addition, it has not been explained how failure and loosening after TKA is caused by PVNS 13 . An idiosyncratic reaction in certain patients to fine wear debris was assumed in the single case described so far 8 .…”
Section: Discussionmentioning
confidence: 97%
“…7 Although it was reported that non-PNVS may occur after replacement knee arthroplasty, 4,7,8 all villonodular synovitis cases after arthroplasty in the English-language literature are pigmented. 3,6,13 …”
Section: Introductionmentioning
confidence: 99%
“…PVNS is a locally aggressive proliferative disorder of the synovium that is a rare complication after TKA [7] , [8] , [9] , [10] , [11] . The etiology of PVNS is unclear, although recurrent hemorrhage, neoplasm, and trauma have been reported as possible causes [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite it being a benign process, recurrence rate after initial resection has been noted between 8% and 60% [6] . PVNS after total knee arthroplasty (TKA) is very rare, with limited case reports available [7] , [8] , [9] , [10] , [11] . Currently there are no published reports describing PVNS 4 years after a primary TKA with recurrent hemarthrosis and no evidence of synovitis 1 year after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al 7 and Brian R. Hamlin et al 8 have reported cases of the failures due to aseptic loosening and recurrence of the disease in case of PVNS. In Mannucci PM et al 3 study, they performed total synovectomy in all patients and they found that in the majority of cases (53%), there was no recurrence of haemarthrosis; in the others, the condition was reduced (40%) or unchanged (7%).…”
Section: Discussionmentioning
confidence: 99%